ML Classification-Based Detection of Cancerous Nodules from Radiology Images - Senthil Kumar, T. K.; Pal, Subhabaha (Indian Journal of Computer Science, 2019)
The appearance of pulmonary nodule is the early manifestation of lung cancer and early detection from the lung CT scan images leads to better treatment. Machine Learning can help in the detection of cancerous nodules. The present paper gives an overview of the machine learning-based modelling for detection of cancerous pulmonary nodules from CT scan images. The paper discusses the whole process involving transformation of the CT scan image, extraction of the nodules and conversion of these into quantitative form and ultimate fitting of suitable classification model for detection of cancerous pulmonary nodule after labelling the nodules.